Oral transit time in children with neurological impairment indicated for gastrostomy - Cola, Paula Cristina; Afonso, Débora [UNESP]; Baldelin, Cleber Gustavo Rotoli; Rubira, Claudio José; de Agostinho, Francisco; da Silva, Roberta Gonçalves [UNESP] (FapUNIFESP (SciELO), 2020)
Purpose: The objective of the present study was to describe the total oral transit time (TOTT) of children with neurological impairment (CNI) and with an indication of gastrostomy. Method: A cross-sectional clinical study was conducted on 15 children (10 male and 5 female ranging in age from 1 to 14 years; mean 5.7 years) with CNI and gastrostomy indication. The patients were monitored by a Multidisciplinary Group of Pediatric Gastroenterology of Universidade de Marilia-UNIMAR, which 13 of them with previous exclusive oral feeding and 2 fed by a nasogastric tube. Swallowing was analyzed by videofluoroscopy swallowing study and 19 images of TOTT were obtained using specific software, with analysis of pureed food (13 images) and liquid (six images). TTOT was categorized as short or long based on definitions already evidenced in the literature. Results: The mean and standard deviation of TOTT values was 10.75 s and 11.76 s for pureed food and 4.22 s and 1.54 s for liquid food. Conclusion: The total oral transit time of pureed or liquid consistency was long in children with neurological involvement and with an indication of gastrostomy.
Keywords: Gastrostomy; Nervous system disease; Quantitative analysis; Swallowing disorders; Time